Acquisition of Goat and Sheep Farming Knowledge and Artificial Insemination Technology of Nanomaterial-Assisted Semen Sexing for Farmers in Wagir District, Malang Regency - Kusumawati, Enike Dwi; Zaini, Akhmad; Sarwoko, Endi; Mahmud, Ali; Meinardhy, Ricky; Ramayanti, Kinta; Pamungkasih, Estri; Ristanti, Rahmadina Fitria; Arini, Iftita Yustitia; Wahyudie, Diyan Eko; Pradana, Diva Cahyo; Fachthurrohman, Muchammad; Ashari, Farhan; Pinastico, Stephanus Herin; Ulum, Muhammad Danial; Nugke, Haydar Wafiq; Kari, Asmad; Komilus, Connie Fay (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
In accordance with the Malang Regency Regional Development Plan, Wagir District is one of the Livestock Centre’s in Malang Regency because of its higher population of goats and sheep. However, the lack of goat and sheep farming knowledge as well as lack numbers of superior quality and quantity of lambs become main problems for realizing that plan. Therefore, a four-helix joint program was conducted through the collaboration of farmer communities, universities, industries, and local government to solve those problems. The community empowerment was aimed to improve the goat and sheep husbandry knowledges and farming skills as well as to train farmers in applying the artificial insemination technology with nanomaterial-assisted semen sexing to improve the availability of superior lambs of goats and sheep and sustaining the quantity and quality of goats and sheep in Wagir District of Malang Regency. The approach of participatory action and learning system was conducted through the community empowerment program, including valuable activities, namely focus group discussion, training, and direct practice, mentoring and field monitoring in 12 villages. The results of this program showed that the farmer awareness, knowledge, and skills on practicing good farming of goat and sheep as well as the application of the artificial insemination technology with nanomaterial-assisted semen sexing increased significantly from 20% to 90%. The social and economic impacts of the application of artificial insemination technology of nanomaterial-assisted sexing semen are the significant increase of goats and sheep farming productivity and the strengthening of livestock business management.